2016
DOI: 10.7759/cureus.853
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Complex Recalcitrant Wounds Treated with Epidermal Grafts Harvested from an Automated Device

Abstract: Introduction: Epidermal grafting has several advantages over full-thickness or split-thickness grafts in the treatment of complex non-healing wounds. These include the low risk of donor site complications, minimal patient discomfort, and abstention from the operating room. Traditionally, the lack of reliable epidermal harvesting techniques has limited its clinical utilization. The development of an automated suction blister epidermal graft (SBEG) harvesting device may facilitate clinical utilization of this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Following full-text review of the remaining 173 articles, 166 articles were excluded as the inclusion criteria were not met. A total of seven articles were included and formed the basis of this systematic review (7,(11)(12)(13)(14)(15)(16) (Figure 2). Cross-checking of the reference list revealed that no article was missed by the initial search.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following full-text review of the remaining 173 articles, 166 articles were excluded as the inclusion criteria were not met. A total of seven articles were included and formed the basis of this systematic review (7,(11)(12)(13)(14)(15)(16) (Figure 2). Cross-checking of the reference list revealed that no article was missed by the initial search.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Wounds with 50--99% healing Cai SS et al, 2016 0.44 (0.14, 0.79) Bhatia A, 2016 0.82 (0.65, 0.93) Costanzo et al, 2006 0.55 (0.36, 0.74) Hentzer B et al, 1975 0.83 (0.52, 0.98) proportion (95% confidence interval) Figure 3 Meta-analysis of proportion of wounds with complete healing (random-effects plot). Proportions are shown with 95% confidence intervals.…”
Section: Use Of Anaesthesiamentioning
confidence: 99%
“…No complications were reported . A study of nine patients showed complete healing after 13 weeks for four and an average reduction of 79% in the surface area of the ulcer, with no complications …”
Section: Discussionmentioning
confidence: 97%
“…4 A study of nine patients showed complete healing after 13 weeks for four and an average reduction of 79% in the surface area of the ulcer, with no complications. 5 Another study with a population of seven patients showed complete healing for six after 4 weeks. 3 Our study is the first to provide results on such a large population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation